Development of Nipa Palm Fruit Toffee Product - Supaking, Janwipa (Journal of Food Technology, Siam University, 2019)
Nipa (Nypa fruticans) is one of mangrove species plant found growing in Phra Samut Chedi district, Samut Prakarn province. An unripe nipa endosperm is popularly consumed as fruit or food. However, an unripe nipa endosperm has a very high moisture content, thus potentially having a short shelf life of 2-3 hours at ambient temperature. The information on the uses of ripe nipa endosperm is also limited. This research aimed to study the five different appropriate ratios of unripe and ripe nipa palm at 100:0, 75:25, 50:50, 25:75 and 0:100 (w/w) on nipa palm fruit toffee product and analysis of product quality. The result indicated that an addition of ripe nipa endosperm affecting on increasing of L*, a*, b*, hardness, cohesiveness, and chewiness, while no significant difference of springiness (p>0.05). Sensory evaluation results showed a decreasing trend in texture scores (p≤0.05), while no significant difference in appearance and flavor score (p>0.05). The 3rd-formula nipa palm fruit toffee was obtained similar sensory scores to the 1st-formula (control). Therefore, the optimum formula of nipa palm fruit toffee consisted of 500 grams of unripe nipa palm, 500 grams of ripe nipa palm, 297.50 grams of sugar, 352.50 grams of glucose syrup, 150 grams of skim milk powder and 80 grams of salted butter. It had 85 ºBrix and 0.585 aw, respectively. Moisture content, carbohydrate, crude protein, total fat, ash and dietary fiber were 3.50%, 85.72%, 7.43%, 2.86%, 0.49%, and 4.45%, respectively. Moreover, the microbiological quality was complied with the Thai Community Product Standard (TCPS 265/2559; Toffee).